Perceptions of interior design students on teaching strategies for deisgn studio courses under remote learning - Orda, Joyce G.; De Leon, Luna Liezl N. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
The sudden shift to online/remote learning brought about by the COVID-19 pandemic had both positively and negatively affected students and teachers in Interior Design education. Implementing effective teaching strategies is important to achieve effective learning for the students in this setup. The purpose of this study was to acquire the perceptions of interior design students on the teaching strategies for design studio courses under the remote learning setup. It also aimed to develop a critical view of the educational situation during the pandemic and its implications for the reopening of face-to-face classes. Factors were examined affecting students' perceptions of teaching strategies, considering existing conditions and personal aspects. These were extracted from the course design and content, instructor support, communication, platforms used, peer interaction, and feedback system that surfaced under this setup. A descriptive qualitative research approach was used to analyze data from twenty (20) UP BSID students enrolled in 2022 and below who were selected purposefully and conveniently through survey questionnaires and individual interviews. In this study, it was found that instructors implemented the most recurring strategies such as leniency in deadlines, setting students their own pace, recorded lectures, and feedback at the end of the semester, in which students perceived negatively. Some were positively perceived such as doing most of activities synchronously, utilizing platform features, and using personal messaging apps for communication, that students also suggested incorporating in blended learning. It was concluded that instructors implemented teaching strategies based on convenience with time, physical effort, and optimal productivity. The study showed that students’ personal living conditions and mental health greatly affect their perceptions.
Thesis
Includes bibliographical references (pages 114-118)
Keywords: Interior decoration -- Philippines. -- Study and teaching (Higher); COVID-19, Pandemic, 2020 - -- Philippines; Distance higher education